Modern Mechanisms of Standardization for Improving the Ecological Situation in the Regions - Arina Yurievna Yanchenko; Natal’ya Vital’evna Androsenko; Galina Nikolaevna Ivanova (Экономика региона, 2018)
The environmental problem concerns everyone. We cannot live in isolation, human activity affects the environment. The article describes the model of modern mechanisms of standardization for successful implementation of the state policy in the sphere of environmental protection in the Russian Federation. As a methodological basis, the authors considered the concept of sustainable development stimulating to implement the nature protection measures. We have analyzed the pollution level in the Russian regions by the man-made impact. The analysis is based on the Russian Meteorological Service data published in the state report. We have defined the most environmentally disadvantaged federal districts. The article considers the environmental problems at the level of the territorial subjects of the Russian Federation. We focus on the influence of demographic problems connected with environmental pollution on the growth rate of regional economy. The article reviews the Russian laws and regulations concerning standardization process, including the procedure for determining the best technology of manufacturing process and/or rendering services. This technology has to be based on the scientific and technological innovations and meet environmental objectives. We have described the international experience in this field, and defined the aspects of environmental regulation from the international practice, which can be applied in the Russian regulatory documents. We have considered the institutional structure as a part of Federal Agency on Technical Regulating and Metrology, which provides expert advice and opinions concerning the drafts of compendiums on the best available technologies. We classify compendiums, which are being currently developed. We have identified the fields of economic activity, which need the development of environmental standards and technology compendiums, which will take into account the volumes of the waste that are subject to neutralization and utilization. We have developed a universal model for the implementation of standardization mechanisms. This model may solve the environmental problems in any region within the developed technical regulation and the nature protection legislation. The universality of the presented model consists in the integrated use of the general system of measures for environment protection in any region. In summary, the results show the need to introduce the standards and the best technology compendiums. It is necessary for the successful implementation of ecologically friendly business practices including power and resource-saving.